2003
DOI: 10.1093/ageing/32.4.442
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of hip protectors for the prevention of second hip fractures

Abstract: this trial does not suggest a benefit of the studied hip protector among people living outside residential accommodation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
14

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 4 publications
1
39
0
14
Order By: Relevance
“…Finally, we have used this approach to highlight the effectiveness of hip protectors in decreasing the risk of hip fractures in a vulnerable, often ignored population with a significant burden of disease. Process of exclusion of studies from the systematic review [26][27][28][29][30][31][32][33][34][35][36]. Table 1 Assessment of the methodologic features of included studies The unit of randomization was not clearly described in the primary publication.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have used this approach to highlight the effectiveness of hip protectors in decreasing the risk of hip fractures in a vulnerable, often ignored population with a significant burden of disease. Process of exclusion of studies from the systematic review [26][27][28][29][30][31][32][33][34][35][36]. Table 1 Assessment of the methodologic features of included studies The unit of randomization was not clearly described in the primary publication.…”
Section: Discussionmentioning
confidence: 99%
“…Hip protectors (115)(116)(117)(118)(119)(120)(121) Hip protectors are a device used to disperse the impact of a fall. The available evidence for hip protectors demonstrates that:…”
Section: What Are the Main Risk Factors For Falls Amongst Older Peoplmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39] In the Cochrane review, 13 the authors concluded that hip protectors were not effacacious in studies randomized by individual patient within an institution, or living independently. In contrast, data from cluster randomized studies indicated that for residents in institutional care, where hip fracture rates are high, hip protectors appeared to reduce the incidence of hip fractures.…”
Section: Commentmentioning
confidence: 99%